The relationship between awareness, compliance cost, biophilic attitude and financial stability on environmental tax compliance - Juhaida Abd Ghani
Environmental taxation is not that familiar among Malaysians as there are no exact charges being recognized as environmental tax imposed in Malaysia. The closest imposed tax which can be associated with environmental tax is petroleum income tax under Petroleum Income Tax Act 1967. Other charges such as quit rent, toll charge, entrance fee, parking, and many more, were imposed to maintain and conserve the environment. Although the government has introduced many campaigns and promotions to protect the environment, data on environmental pollution and degradation in Malaysia still show fluctuation and do not fulfil the Malaysian environment quality standards. Research by EU High Level Groups of Experts on Literacy (2012) revealed that lack of awareness contributes to negative perception and affects negatively on compliance behaviour. This study examines the role of awareness and compliance cost on environmental tax compliance behaviour by introducing the economic affluence and naturalistic behaviour of the tourists. This study instigates that financial strength and natural feeling (Biophilic attitude) towards the environment would influence the positive behaviour towards environmental tax compliance. This is a quantitative approach study with the use of selfadministered questionnaire distributed randomly to approximately 400 local tourists in the East Coast of Peninsular Malaysia, by focusing on tourists at the natural/environmental based tourism spots such as islands, zoos and forest reserve parks. The data were analysed using IBM Statistical Package for the Social Sciences (SPSS) 23 and Smart Partial Least Squares (PLS) 3 for data screening, Confirmation Factor Analysis (CFA), Multigroup Analysis (MGA) and descriptive analysis. This study shows that low awareness contributes to low environmental tax compliance among tourists. Although Biophilic attitude or natural feeling towards the environment alone affects positively on the level of environmental tax compliance, the result is not significant enough to moderate the relationship between awareness and environmental tax compliance. Financial stability, on the other hand, does not influence the level of compliance either directly or as a moderating variable. This study provides insights on the importance of awareness on environmental tax compliance. While other factors appear significant in other studies outside Malaysia, this study finds only awareness, with all its dimensions, affects the level of environmental tax compliance. For future study, it is recommended that other new tax compliance factors are explored in improving the level of environmental tax compliance.